Bułgarska polonistyka ma za sobą piękną i długą tradycję. Wywiad z Agnieszką Kościuszko, dyrektor Instytutu Polskiego w Sofii - Petrowa, Radostina (Postscriptum Polonistyczne, 2020)
Agnieszka Kościuszko, director of Polish Institute in Sofia, presents in this interview main purposes and tasks of this important cultural institution. She shares her impressions of Bulgarian culture and possibilities for partnership between our two countries, describes the most important cultural events and initiatives in recent years and her personal perspective for future work of the Institute.